2005
DOI: 10.1128/iai.73.4.2205-2212.2005
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Gastric Mucosal Cytokine Expression inHelicobacter pyloriGastritis in Mongolian Gerbils

Abstract: Data regarding the chronological changes in gastric mucosal cytokines in the different phases of Helicobacter pylori infection are unavailable. We examined Mongolian gerbils for up to 52 weeks after H. pylori (ATCC 43504) inoculation. Levels of mRNAs of mucosal cytokines (interleukin-1␤ [IL-1␤], gamma interferon [IFN-␥], IL-4, IL-6, and IL-10) were assessed using real-time reverse transcription-PCR. Starting 26 weeks after H. pylori inoculation, two clinicohistologic patterns appeared: gastric ulcers in 32% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 30 publications
3
62
1
Order By: Relevance
“…However, gastric biopsies from persistently infected animals only showed weak gastritis. Yamaoka et al 25 have reported natural history of H. pylori (ATCC43504) induced gastritis and associated gastric mucosal cytokine expression in Mongolian gerbils. In their results, polymorphonuclear and mononuclear cell infiltration was apparent relatively early (8 and 4 weeks after inoculation, respectively) and declined thereafter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, gastric biopsies from persistently infected animals only showed weak gastritis. Yamaoka et al 25 have reported natural history of H. pylori (ATCC43504) induced gastritis and associated gastric mucosal cytokine expression in Mongolian gerbils. In their results, polymorphonuclear and mononuclear cell infiltration was apparent relatively early (8 and 4 weeks after inoculation, respectively) and declined thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a predominantly H. pylori-specific Th1 response, characterized by induction of high level of TNF-a, IL-1b, and IFN-g is associated with H. pylori-infected gastritis. 24,25 COX-2 and iNOS are well known to play important roles in gastric cancer growth and progression. These results indicate that canolol inhibits the mRNA expression of COX-2, upregulated by H. pylori-infection, and might reduce release of prostaglandin E2 from the gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…The culture of H pylori from the gastric mucosa of gerbils was performed as previously described. 9,11 The recovered strains were tested for chloramphenicol resistance to confirm the stability of the mutation for the cagE mutant-infected cases. Polymerase chain reaction (PCR) analysis was also performed for cagE mutants to confirm the preservation of chloramphenicol cassettes inside the target genes as previously described.…”
Section: Time Course and Deathmentioning
confidence: 99%
“…IFN-γ mRNA levels were decreased at 9 months, which differs from previous reports that IFN-γ mRNA levels remained high at 9 months. 9,28 The reason was unclear; however, the IFN-γ mRNA levels correlated well with cellular infiltration, ERK phosphorylation, and AP-1 binding activity. These results are consistent with the fact that the IFN-γ promoter is regulated primarily by AP-1.…”
Section: Expression Of Ifn-γ Il-6 and Kc In Gastric Mucosa Of Mongomentioning
confidence: 99%
See 1 more Smart Citation